(untitled) (Bangladesh Journal of Medical Science, 2015)
Objectives: Hepatitis B virus (HBV) infection is a global health problem with about 2 billion infected persons. Pakistan is one of the endemic areas for viral hepatitis B. Prevention is merely a safe approach rather than curing against high incidence of viral hepatitis. Therefore, the aim of the present study was to assess the knowledge and awareness of HBV infection, its prevention and transmission, perception of HBV vaccine and vaccination status among young females of Karachi, Pakistan. Methods: This cross sectional study was conducted from Oct till Dec 2014 by adopting a pre-validated questionnaire distributed to female individuals in Karachi, Pakistan. Descriptive statistics were used to demonstrate students demographic information and their response to the questionnaire items. Kruskal Wallis H test was executed to evaluate the association of age and educational status of the respondents with their response. A p-value <0.05 was considered as significant. Results: Out of 550 survey questionnaires, only 434 were returned back in useable form. Hence the response rate was 78.9%. More than 90% had knowledge of HBV infection and 85.94% knew that HBV infection can be prevented by vaccination. However, only 17% had received HBV vaccination during childhood. 67.05% and 54.60% knew that HBV can be transmitted from mother to infant and an infected mother may transmit hepatitis B to her newborn baby through breast milk respectively. Only 24% had been tested for HBV in adulthood. General excuses for not having their HBV status tested, were lack of motivation (36.76%) and lack of time to check (21.54%). Conclusion: It indicates that majority of respondents showed some awareness of HBV and its related consequences. Yet, there are some misapprehensions regarding the attitudes that imitate a fallacy perception of the disease. It identifies a more standardized approach coupled with the well-structured health education programs pointing out such misconceptions. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.376-383